Ventricular arrhythmia in heart failure patients with reduced ejection fraction and central sleep apnoea - Fisser, Christoph (ERJ Open Res, 2021)
Cheyne–Stokes respiration (CSR) may trigger ventricular arrhythmia in patients with heart failure with reduced ejection fraction (HFrEF) and central sleep apnoea (CSA). This study determined the prevalence and predictors of a high nocturnal ventricular arrhythmia burden in patients with HFrEF and CSA (with and without CSR) and to evaluate the temporal association between CSR and the ventricular arrhythmia burden.  This cross-sectional ancillary analysis included 239 participants from the SERVE-HF major sub-study who had HFrEF and CSA, and nocturnal ECG from polysomnography. CSR was stratified in ≥20% and <20% of total recording time (TRT). High burden of ventricular arrhythmia was defined as >30 premature ventricular complexes (PVCs) per hour of TRT. A sub-analysis was performed to evaluate the temporal association between CSR and ventricular arrhythmias in sleep stage N2.  High ventricular arrhythmia burden was observed in 44% of patients. In multivariate logistic regression analysis, male sex, lower systolic blood pressure, non-use of antiarrhythmic medication and CSR ≥20% were significantly associated with PVCs >30·h(−1) (OR 5.49, 95% CI 1.51–19.91, p=0.010; OR 0.98, 95% CI 0.97–1.00, p=0.017; OR 5.02, 95% CI 1.51–19.91, p=0.001; and OR 2.22, 95% CI 1.22–4.05, p=0.009; respectively). PVCs occurred more frequently during sleep phases with versus without CSR (median (interquartile range): 64.6 (24.8–145.7) versus 34.6 (4.8–75.2)·h(−1) N2 sleep; p=0.006).  Further mechanistic studies and arrhythmia analysis of major randomised trials evaluating the effect of treating CSR on ventricular arrhythmia burden and arrhythmia-related outcomes are warranted to understand how these data match with the results of the parent SERVE-HF study.